AP-1 and TGFß cooperativity drives non-canonical Hedgehog signaling in resistant basal cell carcinoma - Catherine D. Yao (Nature Portfolio, 2020)
Basal cell carcinoma (BCC) cells with increased nuclear myocardin-related transcription factor (nMRTF) levels are resistant to Smoothened inhibitors, however how MRTF activity is regulated is still elusive. Here, the authors identify a LYPD3+/TACSTD2+/LY6D+ BCC subpopulation of resistant BCC cells where AP-1 and TGFß drive nMRTF activation and amplify noncanonical Gli1 activity